Meaningful informed consent with young children: looking forward through an interactive narrative approach - Mayne, F.; Howitt, C.; Rennie, Leonie (2015)
Ideas about ethical research with young children are evolving at a rapid rate. Not only can young children participate in the informed consent process, but researchers now also recognize that the process must be meaningful for them. As part of a larger study, this article reviews children's rights and informed consent literature as the foundation for the development of a new conceptual model of meaningful early childhood informed consent. Based on this model, an ‘interactive narrative’ approach is presented as a means to inform three- to eight-year-old children about what their participation might involve and to assist them to understand and respond as research participants. For use with small groups, this approach revolves around a storybook based on research-related factual images delivered via interactive (re)telling. This narrative approach to informed consent is unique in its holistic design which seeks to address the specific needs of young children in research.